2018
DOI: 10.2174/0929867324666170705111356
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Approach to Diabetic Cardiomyopathy: A Review of Human Studies

Abstract: The management of DC involves improvement in lifestyle, control of glucose and lipid abnormalities, together with treatment of hypertension and CAD, if present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 101 publications
1
13
0
Order By: Relevance
“…Patients with DCM often do not have heart failure symptoms even when LVW increases in the early stage, but as the disease progresses, cardiac enlargement decreases diastolic left ventricular lling, thereby causing left ventricular diastolic dysfunction. DCM can be seen under cardiac MRI mainly manifested as left ventricular hypertrophy, interstitial and peripheral vascular brosis and microvascular abnormalities [11]. This study found that compared with healthy rats, DCM rats showed a signi cant increase in LVW and a signi cant increase in the ratio of LVW to body weight, which also proved that the increase of LVW in DCM rats was not related to obesity, which was consistent with previous studies [10].…”
Section: Discussionsupporting
confidence: 91%
“…Patients with DCM often do not have heart failure symptoms even when LVW increases in the early stage, but as the disease progresses, cardiac enlargement decreases diastolic left ventricular lling, thereby causing left ventricular diastolic dysfunction. DCM can be seen under cardiac MRI mainly manifested as left ventricular hypertrophy, interstitial and peripheral vascular brosis and microvascular abnormalities [11]. This study found that compared with healthy rats, DCM rats showed a signi cant increase in LVW and a signi cant increase in the ratio of LVW to body weight, which also proved that the increase of LVW in DCM rats was not related to obesity, which was consistent with previous studies [10].…”
Section: Discussionsupporting
confidence: 91%
“…The risk of heart disease increases 2–3 times in diabetic patients. Diabetic mellitus (DM) is a common degenerative chronic metabolic disease that causes considerable negative impacts on health and lifespan with diabetic cardiovascular complications (DCCs) as major causes of death in diabetic population 1 , 2 , 3 , 4 , 5 . Diabetic cardiomyopathy (DCM) is one of the DCCs which literally account for more than 80% of diabetic deaths.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that DCM occurs in approximately 12% of diabetic patients (17). Clinical data suggests that DCM is closely associated with Clinical studies indicate that DCM increases the risk of overt heart failure and induces worse prognosis in diabetic patients (18).…”
Section: Discussionmentioning
confidence: 99%